TELAAH TEORITIK TERHADAP PENERAPAN ASAS PEMISAHAN HORISONTAL DALAM UU No. 4 TAHUN 1996 - Priyo Handoko (Perspektif, 1998)
This essay discusses the principle of Horizontale Separation in Undang-Undang No. 4 Tahun 1996 about Hak Tanggungan (UUHT). The existence of this act is an instruction of the 1960 Undang-Undang Pokok Agraria (UUPA), especially in article 51. As we know, UUPA is made based on Adat Law, so all of act that source from UUPA should follow their idea. The problem in this essay is about inconsistency of Horizontale separation in UUHT. The principle is not applied exactly as in Adat Law, in some case this act tend to vertical separation principle.